Bloom syndrome with myelodysplastic syndrome that was converted into acute myeloid leukaemia, with new ophthalmologic manifestations: the first report from Syria. Issue 12 (5th November 2018) - Aljarad, Sara; Alhamid, Ahmad; Rahmeh, Ahmad Rami; Alibraheem, Abdelaziz; Wafa, Abdulsamad; Alachkar, Walid; Aljarad, Ziad; Aziz, Ghasan
Abstract: Bloom syndrome is a rare autosomal recessive disease, in which BLM gene is mutated, leading to genome instability and proneness to malignancy. It is characterized by short stature, sun-sensitive rash and immunodeficiency. We present a case of bloom syndrome with myelodysplasia complicated by acute myeloid leukaemia. This case has new ophthalmologic manifestations. We confirmed the diagnosis by detection of high rate of sister chromatid exchange. The patient received chemotherapy but did not tolerate it well and developed fungal pneumonia.